Advanced perfluorinated electrolyte with synergistic effect of fluorinated solvents for high-voltage LiNi0.5Mn1.5O4/Li cell. (20th July 2022) - Lu, Hai; Zeng, Fubao; He, Long; Feng, Rui; Yuan, Yan; Zhang, Zhiyun; Liu, Huan; Du, Huiling; Zheng, Bin
Abstract: A series of designed fluorinated electrolytes with single or multiple fluorinated solvents were developed for the application of high-voltage lithium second batteries. The synergistic effect of various fluorinated solvents evidently enhance the reversible capacity, cycle and rate performance of the LiNi0.5 Mn1.5 O4 (LNMO)/Li cell, profitted from superior durability of the electrolyte to resist oxidation (despite weakened ionic conductivity), successful surface modification on the LNMO cathode to suppress parasitic reaction, and improved Li metal compatibility to aviod anode corrosion. Theoretical calculation results reveal that the competitive coordination among different solvents inevitably regulates the solvation structure of Li ion, redox capability of the electrolyte and then interfacial chemistry on both electrodes.